Relationship of accessibility oral health care with sosiodemografi conditions in urban and rural areas of Indonesia, 2018: Pilot Pathfinder Survey - Fuad H. Akbar (Journal of Dentomaxillofacial Science, 2019)
Objective: To know the relation of accessibility oral health care with sociodemographic conditions in urban and rural areas of Gowa Regency, South Sulawesi in 2018.Material and Methods: This study used pilot pathfinder survey, conducted in Gowa Regency in April 2018. The subject consisted of 420 people. Data were collected using Oral Health Special Eurobarometer 330 questionnaire. Data analysis using SPSS 24.0 with Chi-square test and significant value p <0.005.Results: Based on sociodemographic conditions, the main reason most preferred to visit dentist is emergency care (pain). There is a significant relationship between accessibility oral health care with location, education level and income society and there is no significant relationship between accessibility oral health care with age, sex and community work.Conclusion: There is a significant relationship between accessibilit oral health care with sociodemographic conditions in urban and rural areas of Gowa regency 2018.